2017
DOI: 10.3390/v9050100
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Entry of Hepatitis C Virus into Hepatocytes

Abstract: Hepatitis C virus (HCV) is a model for the study of virus–host interaction and host cell responses to infection. Virus entry into hepatocytes is the first step in the HCV life cycle, and this process requires multiple receptors working together. The scavenger receptor class B type I (SR-BI) and claudin-1 (CLDN1), together with human cluster of differentiation (CD) 81 and occludin (OCLN), constitute the minimal set of HCV entry receptors. Nevertheless, HCV entry is a complex process involving multiple host sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 133 publications
(194 reference statements)
0
36
0
Order By: Relevance
“…This process includes particle delivery and capture, complex internalization, and membrane fusion [17]. HBV entry requires a tightly coordinated group of specific viral proteins and multiple host receptors [18]. In the current study, we report that HBV-expression upregulates E-cadherin expression, which acts as a novel host factor that facilitates HBV entry.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This process includes particle delivery and capture, complex internalization, and membrane fusion [17]. HBV entry requires a tightly coordinated group of specific viral proteins and multiple host receptors [18]. In the current study, we report that HBV-expression upregulates E-cadherin expression, which acts as a novel host factor that facilitates HBV entry.…”
Section: Discussionmentioning
confidence: 66%
“…HCV adheres to the cell surface by firstly binding to CD81 and occludin, and subsequent binding to claudin to allow for cell entry [41]. Furthermore, Schulze et al reported that hepatocyte polarization is essential for HBV entry [18]. This group also determined that infected HepaRG cells within hepatic islands are predominantly located at the edges.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN1 plays a role in the cell entry of the HCV [Evans et al., 2007], whereas other entry factors are also required [Miao et al., 2017]. Using constructs to overexpress N‐terminus tagging of CLDN1, it was proposed that CLDN1 interacts with CD81 (another HCV entry factor), favouring virus entry [Harris et al., 2008; Harris et al., 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CLDN1 expression level has been proposed as a prognostic marker of patient survival in renal cell carcinomas [Fritzsche et al., 2008), although it is highly cancer‐type dependent and inverse correlation may also exist [Pyo et al., 2019]. CLDN1 plays also a role in the cell entry of the hepatitis C virus (HCV) [Evans et al., 2007], while other entry factors are also required [Miao et al., 2017]. Using constructs to overexpress tagged versions of CLDN1, it was proposed that CLDN1 interacts with CD81 (another HCV entry factor), favouring virus entry [Harris et al., 2008; Harris et al., 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Yet if HDL and NS1 bind to the same domains on the SRB1 molecule is unknown. In addition, as is the case for HCV entrance, where the successful binding in hepatic cells requires the SRB1, claudin-1, the human cluster differentiation CD81 and occludin as a minimal set of receptors working orchestrated as a multimolecular complex (Miao et al, 2017), SRB1 may not be the only receptor molecule for NS1.…”
Section: Discussionmentioning
confidence: 99%